Aunt Dimity and the wishing well [large type] - Atherton, Nancy (Atherton, Nancy. Aunt Dimity series., 2014)
When a strapping young Australian named Jack MacBride arrives in Finch to wrap up his late uncle's affairs, heads turn in the sleepy English village. And when Lori volunteers to help Jack clear out his uncle's overgrown garden, she laughingly tosses a coin into the garden's old well and makes a wish -- which seems to have come true. Word spreads, and more wishes come true. But as they soon learn, one person's wish is another person's worst nightmare.